(untitled) - Decker, Drew (New York : |b J. , |c c2001, 2001)
GIS users routinely encounter key questions about the data needed for their projects: Where did the data come from? Is this the best data available? How can the data be loaded to make it work? What about creating original data? With a broad range of GIS data options to choose from, knowing how to find, select, and use the most appropriate resources for different purposes is absolutely essential in order to keep costs down and make the most of the technology.
Keywords: Geographic information systems,Hệ thống thông tin địa lý; Information resources,Tài nguyên thông tin